(untitled) (International Journal of Medical and Surgical Sciences, 2014)
The facial lifting show a favorable evolution in the last years; some technical modifications and the mixture with another procedures can make a more favorable results, with predictability and low morbidity. The aim of this paper is to show a mixture of two surgical techniques to obtain complimentary results in facial lifting. The technique of facial lifting with SMAS plication and bichectomy are frequently used in facial plastic surgery; the combined work of both procedures allow a reduction in the adipose tissue in the lateral and middle side of the buccal area, showing better esthetical results with a low morbidity.